IMPIAN PARA TOKOH DALAM CERITA PENDEK â€œTHE GENTLE BOYâ€ DAN â€œTHE AMBITIOUS GUESTâ€ KARYA NATHANIEL HAWTHORNE - LOLOMBULAN, DONY JUSUF (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT The Main Characters Dream in the Short Stories â€œ The Gentle boyâ€ and â€œ The Ambitious Guestâ€ is a skripsi which is to fulfill one of the requirements to achieve the title of Sarjana Sastra. There are two main problems to be analyzed; those are â€œwhat are the main characters dream in the short stories The Gentle Boy and The Ambitious Guestâ€œ and â€œwhat are the leading factors that influence they dreamsâ€. The purposes of this research are to identify and describecharacters dreams, to identify and describe the leading factors that influence their dreams and to compare their dreams. In identifying characters dream, the writer used Stantonsâ€™ theory through the intrinsic to analyzing the character, plot and setting, and for the analyzing data the writer used descriptive method and intrinsic approach. The result of this research show that there are two types to reach human dream, there are the dream that achieved with great effort and helps from the others and the dreams will not accompanied with effort or only false dream. Â  Keywords : Dreams, Intrinsic approach, Short Story, â€œThe Gentle Boyâ€ and â€œThe Ambitious Guestâ€.